Pengaruh Daya Tarik Dan Fasilitas Wisata Terhadap Minat Berkunjung Ulang Melalui Kepuasan Pengunjung (Studi Kasus pada Pengunjung Wisata New Mitra Apel, Kota Batu) - Alnawati, Dinar Eka; Nurhidayah, Nurhidayah; Novianto, Abdullah Syakur (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study was conducted to determine the effect of attractions and tourist facilities on repeat visit interest through visitor satisfaction. The method used in this research is quantitative method with explanatory research type. The population of this study were visitors to New Mitra Apel with a sample size of 70 respondents obtained using non-probability sampling techniques with a purposive sampling approach. This study uses the Structural Equation Modeling (SEM) data analysis method with the help of SmartPLS 3.2.9 software. The results of this study indicate that tourist attraction has no effect on repeat visit interest, tourist facilities affect repeat visit interest, attractiveness and tourist facilities affect visitor satisfaction, visitor satisfaction affects repeat visit interest, attractiveness and tourist facilities affect repeat visit interest through visitor satisfaction. Keywords: Tourism Attractions, Tourism Facilities, Interest in Revisiting, Visitor Satisfaction